Second Language Users' Restriction of Linguistic Generalization Errors: The Case of English Un– Prefixation Development. Issue 3 (25th April 2017) - Zhang, Xiaopeng
Abstract: This study adopted Ambridge's research paradigm to examine the effects of entrenchment, preemption, and verb semantics in second language (L2) acquisition of English un – prefixation. Three groups of Chinese learners of English (second‐ and fourth‐year English majors and teachers of English) rated the acceptability of 48 un – prefixed verbs and their bare forms. Frequency of bare forms (e.g., close ) was a factor associated with the preference of the fourth‐year learners and the teachers to reject ungrammatical un – verbs (e.g., unclose ). However, competing forms (e.g., open ) did not appear to be linked to participants' judgments of the acceptability of ungrammatical un – verbs, lending support to the entrenchment rather than the preemption hypothesis. Ratings of the extent to which verbs incorporate the semantics of un – verbs emerged as significant predictors for the fourth‐year learners' and the teachers' judgements of the acceptability of grammatical un – verbs, supporting the semantic verb class hypothesis. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .